1986
DOI: 10.1099/0022-1317-67-3-453
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antiviral Antibodies with Predetermined Specificity Using Synthetic Peptide-beta-Lactamase Conjugates: Application to Antibodies Specific for the preS Region of the Hepatitis B Virus Envelope Proteins

Abstract: SUMMARYAmino acid sequences coded for by the preS region of the hepatitis B virus (HBV) envelope gene are present both in HBV and in subviral hepatitis B surface antigen (HBsAg) particles. Consequently, anti-preS-specific antibodies are elicited during the course of HBV infection. Such antibodies are virus-neutralizing. Therefore, it is important to determine whether or not vaccination with HBsAg also induces an antipreS-specific immune response. We describe here an enzyme-linked immunosorbent assay applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…It has recently been shown by us that this interac tion occurs not only in vitro [Machida et al, 1984] with glutaraldehyde-treated HSA [Yu et al, 1985] but also in vivo with a not yet identified serum factor , The reported formation of antibodies against HSA during acute and chronic hepa titis suggests that this phenomenon may in duce autoimmune reactions of pathogenetic relevance [Hellstrom et al, 1986], The data on the natural anti-pre-S2 response after hepati tis B infection are contradictory [Hellstrom et al, 1986, Budkowska et al, 1986. The finding of anti-pre-S2 by immunoblot [unpublished data] in late convalescence and in persons who received a pre-S2-containing vaccine [Thomssen et al, 1983] is in agreement with reports [Neurath et al, 1986a] that the major pre-S2 epitopes are also immunogenic in hu mans. In our opinion, the clinical testing of pre-S2-containing vaccines is presently rea sonable if potential autoimmune reactions are carefully monitored.…”
Section: Pre-s2 Antigen As Vaccine Componentsupporting
confidence: 79%
“…It has recently been shown by us that this interac tion occurs not only in vitro [Machida et al, 1984] with glutaraldehyde-treated HSA [Yu et al, 1985] but also in vivo with a not yet identified serum factor , The reported formation of antibodies against HSA during acute and chronic hepa titis suggests that this phenomenon may in duce autoimmune reactions of pathogenetic relevance [Hellstrom et al, 1986], The data on the natural anti-pre-S2 response after hepati tis B infection are contradictory [Hellstrom et al, 1986, Budkowska et al, 1986. The finding of anti-pre-S2 by immunoblot [unpublished data] in late convalescence and in persons who received a pre-S2-containing vaccine [Thomssen et al, 1983] is in agreement with reports [Neurath et al, 1986a] that the major pre-S2 epitopes are also immunogenic in hu mans. In our opinion, the clinical testing of pre-S2-containing vaccines is presently rea sonable if potential autoimmune reactions are carefully monitored.…”
Section: Pre-s2 Antigen As Vaccine Componentsupporting
confidence: 79%
“…In this short review, only peptides as viral antigens will be considered. Although the review focuses on human immunodefi ciency virus (HIV) serology, it should be mentioned that the technique also is effective for the identification of postinfection anti bodies with specificity for, e.g., Epstein-Barr [3], hepatitis B [4] papilloma [5], and respira tory syncytial virus [2], Synthetic peptide antigens offer a number of advantages over other more complex anti gens. There is no need for the handling of infectious virus.…”
mentioning
confidence: 99%